2022
DOI: 10.1186/s40824-022-00316-z
|View full text |Cite
|
Sign up to set email alerts
|

Injectable PTHF-based thermogelling polyurethane implants for long-term intraocular application

Abstract: Background Hydrogels show great potential to be used for intraocular applications due to their high-water content and similarity to the native vitreous. Injectable thermosensitive hydrogels through a small-bore needle can be used as a delivery system for drugs or a tamponading substitute to treat posterior eye diseases with clear clinical potential. However, none of the currently available thermosensitive hydrogels can provide intraocular support for up to 3 months or more. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…While this is true, especially in such a small model, such as in a mouse, advanced methodologies for higher-order animals (i.e., rabbits) have already started to overcome this issue by performing a small vitrectomy before gel injection to reduce the overall pressure. This work showed that such a procedure in the rabbit retina did not lead to inflammation or other damage, opening the possibility for more detailed studies going forward [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this is true, especially in such a small model, such as in a mouse, advanced methodologies for higher-order animals (i.e., rabbits) have already started to overcome this issue by performing a small vitrectomy before gel injection to reduce the overall pressure. This work showed that such a procedure in the rabbit retina did not lead to inflammation or other damage, opening the possibility for more detailed studies going forward [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the influence of MOFs on model Pluronic F127 thermogels established, we investigated the effects of MOF addition on gelation of EPC thermogels (Figure 1). Although Pluronic F127 has been widely studied in drug delivery applications, it still possesses several limitations such as fast erosion rate, high gelation concentration, 59 and low biodegradability. 60 This is due to the low molecular weight and insufficient hydrophobicity of commercial Pluronics, which preclude strong micelle aggregation.…”
Section: Synthesis and Characterization Of Mof−thermogelmentioning
confidence: 99%
“…71 Zhang et al subsequently modified EPC by substituting PCL with poly(tetrahydrofuran carbonate) diol (PTHF) to obtain a thermogel (termed as EPT). 72 PTHF was used because it is structurally similar to PEG and PPG and it is a material that has been previously used for long-term biomedical appli-…”
Section: Reviewmentioning
confidence: 99%
“…This was demonstrated when it was found that EPC degrades completely and becomes undetectable in the vitreous at 3 months post-implantation while about 30% of EPT would still be observable for the same duration. Release kinetic studies performed in vitro with Bovine Serum Albumin (BSA) as a model drug showed that EPT had a consistent protein release profile and was able to release 50% of the loaded amount over 28 days in vitro, which indicates its ability for extended protein release 72 and the potential for long-term anti-VEGFs delivery for the treatment of DR. Another multiblock polyurethane thermogel was fabricated by Park and co-workers consisting of Poly-(N-Boc-serinol) as the hydrophobic block and PEG as the hydrophilic block for the delivery of the anti-VEGF agent, bevacizumab. 73 This biodegradable PEG-poly-(serinol hexamethylene urethane) (ESHU) thermoresponsive hydrogel could be injected at 15 wt% polymer in PBS solution or a solution of bevacizumab in its sol state and undergo a rapid sol-gel phase transition at 37 °C.…”
Section: Rsc Applied Polymersmentioning
confidence: 99%
See 1 more Smart Citation